Serial combination of non‐invasive tools improves the diagnostic accuracy of severe liver fibrosis in patients with NAFLD. Issue 6 (27th July 2017) - Petta, S.; Wong, V. W.‐S.; Cammà, C.; Hiriart, J.‐B.; Wong, G. L.‐H.; Vergniol, J.; Chan, A. W.‐H.; Di Marco, V.; Merrouche, W.; Chan, H. L.‐Y.; Marra, F.; Le‐Bail, B.; et al.
Summary: Background: The accuracy of available non‐invasive tools for staging severe fibrosis in patients with nonalcoholic fatty liver disease (NAFLD) is still limited. Aim: To assess the diagnostic performance of paired or serial combination of non‐invasive tools in NAFLD patients. Methods: We analysed data from 741 patients with a histological diagnosis of NAFLD. The GGT/PLT, APRI, AST/ALT, BARD, FIB‐4, and NAFLD Fibrosis Score (NFS) scores were calculated according to published algorithms. Liver stiffness measurement (LSM) was performed by FibroScan. Results: LSM, NFS and FIB‐4 were the best non‐invasive tools for staging F3‐F4 fibrosis (AUC 0.863, 0.774, and 0.792, respectively), with LSM having the highest sensitivity (90%), and the highest NPV (94%), and NFS and FIB‐4 the highest specificity (97% and 93%, respectively), and the highest PPV (73% and 79%, respectively). The paired combination of LSM or NFS with FIB‐4 strongly reduced the likelihood of wrongly classified patients (ranging from 2.7% to 2.6%), at the price of a high uncertainty area (ranging from 54.1% to 58.2%), and of a low overall accuracy (ranging from 43% to 39.1%). The serial combination with the second test used in patients in the grey area of the first test and in those with high LSM values (>9.6 KPa) or low NFS or FIB‐4 values (<−1.455 and <1.30, respectively) overall increased the diagnostic performance generating an accuracy ranging from 69.8% to 70.1%, an uncertainty area ranging from 18.9% to 20.4% and a rate of wrong classification ranging from 9.2% to 11.3%. Conclusion: The serial combination of LSM with FIB‐4/NFS has a good diagnostic accuracy for the non‐invasive diagnosis of severe fibrosis in NAFLD. Abstract : Linked Content This article is linked to Khan paper. To view this article visithttps://doi.org/10.1111/apt.14267 .